Modern approaches of diagnosis and criteria for assessing the limitations of life activities in adolescents with mild mental retardation - V. L. Pidlubnyi; S. O. Chabaniuk (Kazimierz Wielki University, 2021)
Among the forms of mental pathology that are found in childhood, mental retardation (MR), which makes a significant contribution to the rates of morbidity and disability, occupies a special place. In order to investigate modern approaches and the criteria for diagnosis and assessment of limitations of life with mild MR in adolescents, on the basis of the Kryvyi Rih (Ukraine) neuropsychiatric dispensary, a two-stage clinical-epidemiological, clinical-psychopathological and psychodiagnostic study of 154 people born in 2003-2008 with mild MR was carried out. According to the results of the study, a number of factors that directly affect the quality of life of adolescents with mild MR have been established, among them: underdevelopment of cognitive forms of mental activity (in the forms of violations of logical thinking, slowing down of processes of generalization and comparison), slow pace of thinking and inertia of thought processes (which makes impossible to transfer the skill acquired in the learning process to new conditions), underdevelopment of thinking with a decrease in the function of attention (which leads to underdevelopment of complex emotions and arbitrary forms of behavior), mental underdevelopment in combination with impaired motor skills, speech, memory, attention and emotional sphere.